Analysis and Design of Regional Tourism Information System “SIPARDA” of Morotai Island Regency - Yerik Afrianto Singgalen (Universitas Bina Darma, 2022)
The analysis and design of the regional tourism information system known as SIPARDA is a follow-up to the results of the strategic planning of the information system to optimize the performance of the bureaucracy, especially the Tourism Office of Morotai Island Regency, related to the main tasks and functions of the destination and tourism industry, tourism marketing, and creative economy. SIPARDA's design was carried out using the concept of Software Development Life Cycle (SDLC) through a waterfall approach. The application design method begins with identifying user needs and designing a tourism information system relevant to the main tasks and functions of the Tourism Office in the Morotai Island Regency. Unified Modeling Language (UML) is used to describe the business processes of SIPARDA. Five primary actors can operationalize the system: the head of the tourism officer, tourism industry and destination department, tourism marketing department, creative economy department, and administrator. Thus, each department can document attractions, amenities, accessibility, and accommodation data in the Morotai Island Regency as a regional tourism development decision-making database.